2012
DOI: 10.4103/0976-3147.102617
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural angiolipoma: A rare cause of spinal cord compression

Abstract: Spinal epidural angiolipomas are rare, benign tumors composed of mature lipocytes admixed with abnormal blood vessels. Only 128 cases of spinal epidural angiolipomas have been reported in literature till now. Spinal angiolipomas are predominantly located in the mid-thoracic region. We report a case of dorsal epidural angiolipoma in a 56-year-old male who presented with paraparesis and was diagnosed to have D4-5 epidural angiolipoma. Total surgical excision of the epidural angiolipoma was done and his parapares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The subcutaneous region of the trunk, neck and extremities are the places where they generally settle. They may be visible in any part of the body (2). The most frequent settling place is particularly the forearm; almost two third of the angiolipomas are seen here (3).…”
mentioning
confidence: 99%
“…The subcutaneous region of the trunk, neck and extremities are the places where they generally settle. They may be visible in any part of the body (2). The most frequent settling place is particularly the forearm; almost two third of the angiolipomas are seen here (3).…”
mentioning
confidence: 99%
“…Magnetic resonance imaging is the modality of choice when diagnosing spinal angiolipoma. [4][5][6] On MRI, angiolipomas are iso-or hyperintense on T1-weighted images and variable on T2-weighted images but usually hyperintense. The degree of central hypointensity on T1-weighted images is predictive of the degree of vascularity; 5,13 therefore, heterogeneous hyperintensity lesions with focal hypointensity on T2-weighted images should suggest a diagnosis of acute/ hyperacute spinal epidural hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Noninfiltrating angiolipomas are well defined and separate from the surrounding tissue and can usually be easily removed via laminectomy and dissecting techniques. Infiltrating spinal angiolipomas ideally require a wider resection; 4,5 however, even cases of subtotal resection of the infiltrating variant reportedly have good outcomes 17 in terms of spinal cord decompression. One case of preoperative embolization of an infiltrating angiolipoma has been previously described, and the authors reported that this maneuver allowed complete removal with minimal intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations